Sphingobacterium sp. BHU-AV3 Induces Salt Tolerance in Tomato by Enhancing Antioxidant Activities and Energy Metabolism - Vaishnav, Anukool; Singh, Jyoti; Singh, Prachi; Rajput, Rahul Singh; Singh, Harikesh Bahadur; Sarma, Birinchi K. (Frontiers in Microbiology, 2020)
Salt tolerant bacteria can be helpful in improving a plant’s tolerance to salinity. Although plant–bacteria interactions in response to salt stress have been characterized, the precise molecular mechanisms by which bacterial inoculation alleviates salt stress in plants are still poorly explored. In the present study, we aimed to determine the role of a salt-tolerant plant growth-promoting rhizobacteria (PGPR) Sphingobacterium BHU-AV3 for improving salt tolerance in tomato through investigating the physiological responses of tomato roots and leaves under salinity stress. Tomato plants inoculated with BHU-AV3 and challenged with 200 mM NaCl exhibited less senescence, positively correlated with the maintenance of ion balance, lowered reactive oxygen species (ROS), and increased proline content compared to the non-inoculated plants. BHU-AV3-inoculated plant leaves were less affected by oxidative stress, as evident from a reduction in superoxide contents, cell death, and lipid peroxidation. The reduction in ROS level was associated with the increased antioxidant enzyme activities along with multiple-isoform expression [peroxidase (POD), polyphenol oxidase (PPO), and superoxide dismutase (SOD)] in plant roots. Additionally, BHU-AV3 inoculation induced the expression of proteins involved in (i) energy production [ATP synthase], (ii) carbohydrate metabolism (enolase), (iii) thiamine biosynthesis protein, (iv) translation protein (elongation factor 1 alpha), and the antioxidant defense system (catalase) in tomato roots. These findings have provided insight into the molecular mechanisms of bacteria-mediated alleviation of salt stress in plants. From the study, we can conclude that BHU-AV3 inoculation effectively induces antioxidant systems and energy metabolism in tomato roots, which leads to whole plant protection during salt stress through induced systemic tolerance.